Utilizing apolipoprotein E genotypes and associated comorbidities for the assessment of the risk for dementia - Tung, Hsin; Lin, Ching-Heng; Chen, Yi-Ming; Lee, Wei-Ju; Chien, Li-Sheng; Sun, Ting-Hsuan; Liao, Cai-Sian; Lin, Yung-Yang; Hsiao, Tzu-Hung (Frontiers in Aging Neuroscience, 2022)
Dementia is associated with many comorbidities while being related to Apolipoprotein E (ApoE) polymorphism. However, it is unclear how these clinical illnesses and genetic factors modify the dementia risk. We enrolled 600 dementia cases and 6000 gender and age matched, non-dementia controls, with identified ApoE genotype (ε4/ε4, ε4/ε3, and ε3/ε3). Eight comorbidities were selected by medical records, and counted if occurring within 3 years of enrollment. The dementia group had a higher ratio of carrying ε4 allele and prevalence of comorbidities than the non-dementia group. They were also divided into three groups by age: younger than 65, 65-75, and older than 75 years-old. Homozygous ε4 carriers presented persistently high dementia risk throughout three age groups with the odds ratio (OR) around 4.1–6.6. The risk only emerged after 65 years of age in ε3/ε4 subjects with OR around 1.6–2.4. Cerebrovascular accident (CVA) is the commonest comorbidity (14.6%). CVA, sleep disorder, and functional gastrointestinal disorders remained as significant risk comorbidities for dementia throughout all age groups (OR = 1.7–5.0), suggesting comorbidities could also be predictors of dementia. When functional gastrointestinal disorder and ε4 allele both occurred, the dementia risk exceeded the summation of individual risks (OR = 3.7 and 1.9 individually, OR = 6.0 for the combination). Thus, it might be an important comorbidity to predict dementia in ε4 allele carriers. Combining the genetic and clinical information, we detected cognitive decline and optimize interventions early when the patients present a specific illness in a particular age and carry a specific ApoE allele.